Perceptions of Women English Language Teachers on Professional Development: A Narrative Inquiry - KC, Kamala (Curriculum Development Journal, 2023)
Education is one of the key components of human civilization. Both educated women and men contribute for a better world, therefore, equal opportunity in education is a must. In the case of academia, if teachers, both women and men, develop their professional skills, it will benefit the nation’s educational system. This research aimed at exploring the perceptions of women English language teachers on teacher professional development. This study was conducted with purposely selected four women English language teachers teaching at the secondary level in community schools in Rupandehi district. I used interpretive research methodology in this study. I collected data using an interview. In-depth interviews were taken about their personal and professional life-history. Data was transcribed, analysed, categorized and coded to reach the meaning making process. The findings revealed that the participants have good perceptions of teacher professional development. For them, teacher professional development entails upgrading professionalism, learning and sharing the art of teaching through formal and informal TPD platforms, and bringing positive change in students’ outcome. The study has implications for policymakers, curriculum developers, syllabus designers, administrators and teacher educators.